Relationship between changes in blood glucose, glycosylated hemoglobin [HbA1c], cholesterol, and triglyceride and changes in hepatic enzymes: Relationship between some biochemical factors and hepatic enzymes - Mehrdar, Mahboobeh Talebi; Lu, Wei; Rahanjam, Adel (Cellular and Molecular Biology, 2024)
The main risk factors for non-alcoholic fatty liver disease (NAFLD) are strongly associated with obesity, diabetes, hyperlipidemia, and metabolic syndrome. The best clinical evaluation of the liver is done through studying changes in liver enzymes’ activity, especially alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase. Therefore, this study aimed to investigate the relationship between changes in factors such as blood glucose, cholesterol, glycosylated hemoglobin, and triglyceride and changes in hepatic enzymes in patients who visited Fajr Hospital in Tehran. Samples with SGPT levels > 40 U/L were selected and blood samples from the same individuals were collected in the next testing which was six months later. The changes in four factors of blood glucose, glycosylated hemoglobin, cholesterol, and triglyceride were calculated in these two consecutive visits, and finally, they were compared with changes in the hepatic enzymes and the relationship between them was evaluated by SPSS V. 23. Fifty-seven individuals with a mean age of 48 ± 15 years and SGPT > 40 U/L were included in the present study. Six samples were female (10.52 %) and 51 samples were male (89.48 %). The results showed that there was no significant relationship between blood glucose and glycosylated hemoglobin changes and hepatic enzymes. However, there was a significant relationship between cholesterol and triglyceride changes and hepatic enzymes of SGPT and SGOT (p ˂ 0.05). Based on the results of the current study, changes in FBS and HbA1c in two consecutive visits cannot be used to follow up on the treatment of fatty liver. However, changes in cholesterol and triglyceride can be used for monitoring the treatment in people with abnormal levels of hepatic enzymes.